2002
DOI: 10.2166/wst.2002.0376
|View full text |Cite
|
Sign up to set email alerts
|

Downstream flow event sampling of acid mine drainage from the historic Mt Morgan Mine

Abstract: Numerous scientific reports concur that the Dee River is heavily impacted by acid mine drainage from the historic gold and copper mine at Mt Morgan, Central Queensland. The water quality along the Dee River, for 18 km downstream of the mine she to is junction with Fletcher Creek, is characterised by low pH, typically 2.8 to 4.2. With respect to metal concentrations, the Dee River has been described as one of Australia's most polluted rivers. Measurements of pH along the Dee River clearly demonstrated the movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our test case demonstrated that ATPs were able to both support and contradict a priori hypotheses about the stressors causing impact in particular rivers. For example, the existence of an acid-tolerant fauna in the River Dee downstream of the Mount Morgan mine confirms the view of Taylor et al (2002) that low pH is a major cause of impact in this river, in association with high metal concentrations. Conversely, the lack of a shift to a more hypoxiatolerant fauna in Gowrie Creek downstream of the sewage discharge implied that low DO is not likely to be a principal cause of impact in this system, a finding reinforced by Cosser's (1988) observation of a lack of pronounced oxygen depletion.…”
Section: Potential Application Of Tolerance Profilessupporting
confidence: 64%
See 2 more Smart Citations
“…Our test case demonstrated that ATPs were able to both support and contradict a priori hypotheses about the stressors causing impact in particular rivers. For example, the existence of an acid-tolerant fauna in the River Dee downstream of the Mount Morgan mine confirms the view of Taylor et al (2002) that low pH is a major cause of impact in this river, in association with high metal concentrations. Conversely, the lack of a shift to a more hypoxiatolerant fauna in Gowrie Creek downstream of the sewage discharge implied that low DO is not likely to be a principal cause of impact in this system, a finding reinforced by Cosser's (1988) observation of a lack of pronounced oxygen depletion.…”
Section: Potential Application Of Tolerance Profilessupporting
confidence: 64%
“…The more exposed fauna in the River Dee also had ATPs indicating greater tolerance of hypoxia, suggesting that mine drainage might have reduced DO concentrations in this river system as well as pH. However, Taylor et al (2002) reported only moderately low DO levels in the River Dee, and as noted above, the existence of a fauna tolerant of a stressor admits but does not require the presence of that stressor.…”
Section: Response Of Tolerance Profiles To Disturbancementioning
confidence: 70%
See 1 more Smart Citation
“…Such contamination affects between 5000 and 10 000 miles of streams in the western United States (US Department of Agriculture, 1997). Although the most frequent examples of AMD contamination come from the USA and Canada (Grout et al, 2001;Lefevre et al, 2001), this problem also affects numerous states in Africa (Bullock et al, 1997;Geldenhuis et al, 1998), Europe (Banks et al, 1997;Hoth et al, 2001;Dinelli et al, 2002;Grande et al, 2003a,b;Sáinz et al, 2002), Australia (Lottermoser et al, 1999;Taylor et al, 2002) and, in general, wherever there is an intense mining activity in deposits with a presence of sulphides, as is the case not only of pyrite mining, but also of gold, silver, copper, zinc, lead, uranium and coal. In active mines of the developed countries, mining operators treat their effluents before releasing them to the environment.…”
Section: Fluvial Contaminationmentioning
confidence: 99%
“…These factors are geographically variable and therefore it is expected that the characteristics of AMD vary from place to place. While there have been numerous studies on AMD, most of the work was conducted in the developed world such as the United States, Canada, Australia and European countries [10][11][12][13][14][15], with little information in literature being available for Asia, Africa and South America. In some developing countries, illegal mining that operates without consideration of environmental protection is common.…”
Section: Introductionmentioning
confidence: 99%